Analisis Kualitas dan Kuantitas Tenaga Keperawatan Terhadap Persepsi Insiden Keselamatan Pasien di RS X Jakarta Tahun 2015 - Friyanti, Evelyne Sumihar (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
Patient safety has become a very important issue in health care. Everyone wants to get health care that is safe and free from unwanted injuries. Through this study, analyzed the quality and quantity of nurse perceptions of patient safety incidents in the hospital X. The study was conducted on 44 nurses and midwives using cross sectional design to examine the relationship between the variables of knowledge, education, ease of use tools, work experience, discipline and the number of nurses on patient safety incidents.